2002
DOI: 10.1097/00000542-200205000-00034
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Combined with Morphine for the Management of Pain in an Opioid Addict

Abstract: Despite uncertainty as to the absolute values that should be cause for alarm, the sudden precipitous and unilateral rSO 2 decrease prompted sufficient alarm to change the sequence of the surgery. It is our belief that the cerebral oximeter enabled early detection of hemispheric ischemia and prevented what could have been a prolonged ischemic insult if the course of the operation had not been altered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
4

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 6 publications
(6 reference statements)
0
11
0
4
Order By: Relevance
“…Adding ketamine infusion at 10 mg/h to balanced analgesia with epidural local anesthetic, systemic fentanyl and oral naproxen improved pain relief after multiple bony fractures in an opioid addict [19]. Haller et al have shown that ketamine 2.5 mg/kg/min IV infusion reduced IVPCA morphine consumption after spinal fusion in a patient with chronic opioid abuse [20]. In this study, no improvement on pain scores or opioid consumption could be shown with ketamine added to multimodal postoperative analgesic regimen, which we have been using in our institute for years.…”
Section: Discussionmentioning
confidence: 99%
“…Adding ketamine infusion at 10 mg/h to balanced analgesia with epidural local anesthetic, systemic fentanyl and oral naproxen improved pain relief after multiple bony fractures in an opioid addict [19]. Haller et al have shown that ketamine 2.5 mg/kg/min IV infusion reduced IVPCA morphine consumption after spinal fusion in a patient with chronic opioid abuse [20]. In this study, no improvement on pain scores or opioid consumption could be shown with ketamine added to multimodal postoperative analgesic regimen, which we have been using in our institute for years.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a dexmedetomidine infusion may be started [ 64 ] . Nonopioid analgesic adjuvants [NSAIDS, cyclooxygenase-2 inhibitors, ketamine, clonidine (0.1 mg/h)] may be used to reduce opioid dose requirements and provide analgesia during and following surgery [65][66][67][68][69] .…”
Section: Management Of Opioid Tolerancementioning
confidence: 99%
“…Most patients were receiving opioids in conjunction with ketamine and the authors suggest that one of the actions of the drug may be related to the prevention of opioid tolerance. Ketamine has proven useful when managing pain in an opioid addict because of its ability to reverse tolerance (Haller et al 2002). Subramaniam et al (2004) investigated the efficacy and safety of adding low-dose ketamine as an adjuvant to perioperative opioid-based analgesia.…”
Section: The Potential Role Of Ketamine In Chronic Post-surgical Painmentioning
confidence: 99%